Halal food for just and equitable world: Malaysian perspectives - Ramli, Noriah; Amin, Naemah (2007)
Halal and non-halal is very important matter for Muslim consumers all over the world. However with advances in science and technology they are now facing difficulty in choosing genuine halal food. Thus it has become increasingly important that Musllim consumers understand to interpret food labels and gain knowledge on food ingredients. Nowadays food has to undergo many processes and distribute to different parts of the world. In the last century, many Muslims have consumed food claimed to be halal but adulterated with pork, alcohol and non-halal ingredients and additives. As such, food labeling, processing, packaging and new technologies became contentious issues to the Muslims. This paper aims to highlight various legal issues pertaining to production of halal food in Malaysia. These include the issue of halal certification, labeling, enforcement, conflict of jurisdiction between Federal and State authorities and consumer protection. The paper also analyses the adequacy and weaknesses of the existing legal mechanisms and proposes necessary reform for the enhancement of halal food production in view of Malaysia's aim to become the halal hub for international market.